Analysis of Football School Japar Sidik Coach Training on Handling & Preventing Anxiety in Players Aged 10 & 12 Years - Gari Abdilah; Ayi Suherman; Tedi Supriyadi (Journal of Physical Education Health and Sport, 2026)
Anxiety is a psychological disorder that can affect the performance of football players in training or competition. This can result in players experiencing anxiety being unable to play as usual and losing focus and self-confidence, causing them to perform poorly during training and competition. This anxiety requires special attention and appropriate treatment because this phase is an important stage in developing players at an early age. This study aims to analyse the training methods used by Ssb Japar Sidik coaches for 10 and 12 year olds in handling and preventing anxiety. This study uses a qualitative approach with a case study design involving 2 coaches and 8 Ssb Japar Sidik players as research subjects. Data analysis was carried out using Nvivo 12 Pro software to identify patterns and main themes in the research results. The results of this study found that there were 6 main findings in handling and preventing anxiety carried out by Ssb Japar Sidik coaches, namely communication, mental reinforcement, positive psychological environment, mental formation, social support, and special training methods. This research contributes to improving the mental health of young players and developing a structured mental training model for young players in an effort to support football coaching that is oriented towards performance and the psychological well-being of players.